Analisis Kemampuan Lari Jarak Pendek Pada Siswa Kelas V Madrasah Ibtidaiyah Swasta 01 Lebong - Rizky, Miftahur Rezeki; Perdima, Feby Elra; Anggara, Deffri (Journal Of Dehasen Educational Review, 2023)
Running is an accelerated step so that when running there is a tendency for the body to float. This means that when running, both feet do not touch the ground or at least when the feet remain on the ground Handoyo in Jafar (2022: 8).Running numbers are numbers that are referred to as non-technical, because running is a relatively simple natural activity when compared to pole vault numbers or hammer throw numbers (Sidik, 2014: 1). The method in a study is needed to measure whether or not the assessment will be carried out by a researcher. So it is expected that with a good and correct research method will get coherent and accurate results. This type of research is a qualitative approach. The method used in this research is descriptive method. According to Sukardi (2016: 52) descriptive method is a method used to describe and interpret objects as they are. In this study, the descriptive method was used to obtain a description of the short distance running ability of Class V students of Madrasah Ibtidaiyah Swasta 01 Lebong. The method used in this research is descriptive method. According to Sukardi (2016: 52) descriptive method is a method used to describe and interpret objects as they are. In this study, the descriptive method was used to obtain a description of the short distance running ability of Class V students of Madrasah Ibtidaiyah Swasta 01 Lebong. Based on the research data for the speed score, it was found that the highest score was 3.52 and the lowest score was 5.95. From the data analysis, the mean was 4.59, the standard deviation was 0.60, the median was 4.78, and the mode was 4.92. Based on the calculations listed in Table 4, it can be seen that: 5 people or (8.7%) were in the interval class 3.52-3.96, 11 people or (47.83%) were in the interval class 4.42-4.86, 6 people or (26.08%) were in the interval class 4.87-5.31, and 1 person or (4.35%) was in the interval class 5.77-6.21. Running will feel heavier than running on a flat area or on a real track. Therefore, when running training feels heavy, it will feel light when running on the real track, so that it can improve students' 50 meter running ability and can create better running travel times.